5-benzyl-4-phenyl-2,4-dihydro-1,2,4-triazole-3-thione - Akkurt, M; Öztürk, S; Servi, S; Cansiz, A; Sekerci, M; Kazak, C (Int Union Crystallography, 2004)
As part of structural studies of 1,2,4-triazole derivatives, the crystal structure of the title compound, C15H13N3S, has been investigated. The structure shows a V-shape in the molecular skeleton, as found for similar compounds. The crystal structure is stabilized by an N-H...S and three C-H...pi intermolecular interactions.